2019
DOI: 10.1111/apm.12969
|View full text |Cite
|
Sign up to set email alerts
|

Obligate anaerobes are abundant in human necrotizing soft tissue infection samples – a metagenomics analysis

Abstract: Necrotizing soft tissue infections (NSTIs) are associated with high morbidity and mortality and are increasing in incidence. Proper identification of the microbial causes of NSTIs is a crucial step in diagnosis and treatment, but the majority of data collected are culture based, which is biased against fastidious organisms, including obligate anaerobes. The goal of this study was to address this gap in knowledge by characterizing NSTI microbial communities through molecular diagnostics. We performed 16S rRNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…They can be further divided by tissue layer, such as necrotizing fasciitis when involving fascia or myositis when involving muscle, or by anatomic location, such as Fournier gangrene when present in the genitalia and perineum [1][2][3][4]. These infections are polymicrobial up to 80% of the time, with a predominance of group A Streptococcus (GAS), Staphylococcus aureus, Enterococcus, and multiple anaerobic bacterial species [2,[5][6][7].…”
mentioning
confidence: 99%
“…They can be further divided by tissue layer, such as necrotizing fasciitis when involving fascia or myositis when involving muscle, or by anatomic location, such as Fournier gangrene when present in the genitalia and perineum [1][2][3][4]. These infections are polymicrobial up to 80% of the time, with a predominance of group A Streptococcus (GAS), Staphylococcus aureus, Enterococcus, and multiple anaerobic bacterial species [2,[5][6][7].…”
mentioning
confidence: 99%
“…2 Prevotella denticola is an anaerobic gramnegative bacterium that is usually found in periodontal abscesses and head and neck necrotizing fasciitis. 3 These bacteria were sensitive to his antibiotic regimen, and repeat tissue cultures from serial wound debridement showed no bacteria growth. Therefore, antibiotics were not indicated at discharge, and plastic surgery was able to close the large wound defect.…”
Section: Discussionmentioning
confidence: 98%
“…It was recently shown that necrotizing soft tissue infections (NSTIs), infamous for their high patient morbidity and mortality, contain several species of anaerobes, many of which are difficult to culture. Furthermore, 16s rRNA sequencing revealed a more diverse bacterial community than attempts at culturing displayed [ 8 ]. Bessa et al collected samples from 217 chronically infected wounds which showed infections from 28 different species of bacteria.…”
Section: Many Infections Are Polymicrobialmentioning
confidence: 99%